Carbon Liability, Market Price Risk and Social Impact of Reducing Emission from Deforestation and Forest Degradation (REDD) Programme - Dhakal, Bhubaneswor (Journal of Forest and Livelihood, 2009)
This paper analyzes the issues of the proposed Reducing Emission from Deforestation and Forest Degradation (REDD) programme in developing countries. Issues analyzed include carbon liability, market prices and the social impacts of REDD. The analysis on the liability issue shows that forest used in carbon credit sales is likely to be locked into the market for the long term even on subnormal credit market prices. There is also high risk associated with the price of credits. The net revenues from the sale of the forest carbon credits are likely to be meagre for forest dependent people. This paper argues that the REDD programme is highly inappropriate in developing countries where people have limited access to alternative income and employment opportunities. It also seems to pose a big barrier for post?conflict reconstruction in countries like Nepal. Key words: REDD, carbon trade, cartel, livelihood, governance, institutional change Full text is available at the ForestAction website Journal of Forest and Livelihood 8(1) February 2009 pp.67-76